What are lay UK public perceptions of frailty: a scoping review. (1st April 2023) - Shafiq, Shabana; Haith-Cooper, Melanie; Hawkins, Rebecca; Parveen, Sahdia
Abstract: Rationale and objective: Perceptions of frailty can influence how families cope, quality of life and access to support services. Yet little is known of how lay members of the UK general public perceive frailty. This scoping review aimed to explore how frailty is perceived among the lay public in the United Kingdom. Methods: The established scoping review methodology by Arksey and O'Malley was followed and searches were conducted across eight electronic databases and grey literature websites for articles published between 1990 and August 2022. In total, 6, 705 articles were identified, of which six were included in the review. Data were analysed using Braun and Clarke's thematic analysis framework. Results: Three key themes were identified; frailty as a normal part of ageing, perceived consequences of frailty and coping with frailty. Overall, frailty has negative connotations and is perceived as linked to a natural part of the ageing process, increased dependency, loss of identity and social exclusion and stigma. However, it is unclear whether these perceptions have a direct bearing on access to support services for communities. Conclusion and implications: This review identifies that it is imperative for health and social care service providers to consider the individual meaning of frailty for older people and families, to understand and integrate their particular needs and preferences when planning and delivering person centred frailty care and support. There is also a need for development of interventions that focus on increasing education and reducing stigma around frailty in order to change frailty perceptions in the UK.